MENGHADAPI KAPITALISME: PENDEKATAN ECO-SUFISM DALAM GERAKAN ENVIRONMENTALISME ISLAM INDONESIA - Imamah, Fardan Mahmudatul (IAIN Tulungagung, 2017)
The issues of environmental degradation as well as global warming aren?t merely about environmentalism reaction?s activities, but also dealing with the demands of capitalism that keep asking the needs of human life. The need invites exploitation of natural resources as quickly and thoroughly at any time in various places. It has an impact on the declining quality of the environment and natural disasters to social conflict. The function of religion as a source of ethics and morals get the right and significant momentum in addressing the issues described above. Sufism, in particular, as a source of Islamic values ??and attitudes 'restraint' and see everything created by God as part of His power, so that gave birth to its moral responsibility to the environment and the universe. This paper will elaborate the rethinking of the doctrine of enviromental theologians followed by the mapping of the environmental movement of the Muslim?s environment in recent time. The main purpose of this paper is to encourage the main idea of ?eco-Sufism? through ?eco-pesantren?, so it ingrained the culture of being devout Muslims are Muslims that dedicated to the environment. Keywords: eco-sufism, capitalism, pesantren, environment.